Direct puncture embolization using N-butyl cyanoacrylate for a hepatic artery pseudoaneurysm. Issue 2 (March 2014) - Yagi Yoshida, Rie; Kariya, Shuji; Nakatani, Miyuki; Komemushi, Atsushi; Kono, Yumiko; Tanigawa, Noboru
Abstract Massive hemobilia caused by hepatic artery pseudoaneurysm is an uncommon but potentially fatal complication that can occur after biliary intervention. Previous intervention or surgery, atherosclerotic disease, inflammation and even anatomic variants may make the pseudoaneurysm inaccessible to transcatheter approach, therefore it is not always feasible. The present report describes a case of successful embolization of a hepatic artery pseudoaneurysm with N-butyl cyanoacrylate via direct puncture as an alternative approach. The case presentation is followed by the technical points and the properties of N-butyl cyanoacrylate that are particularly advantageous for use in direct puncture procedures.